A bibliometric analysis of the scientific literature on dental implants in large animal models - Matos, F. G.; Stremel, A. C.A.; Lipinski, L. C.; Cirelli, J. A. [UNESP]; Dos Santos, F. A. (My University, 2023)
Aim This bibliometric review aims to report and discuss the main bibliographic characteristics of the scientific literature on dental implants in large animal models. Material and Methods This review followed the Preferred Reporting for Systematic Reviews and Meta-Analyses guidelines, and searches were performed until March/2023 in multiple databases such as Pubmed, Scopus, Scielo, Web of Science, Embase, Science Direct, Brazilian Bibliography of Dentistry, Latin American and Caribbean Health Sciences Literature, Directory of Open Access Journals, and Abstracts Database of Reviews of Effects, in addition to gray literature. Results A total of 2,618 articles were found, of which 70 were eligible. The majority of these articles were published in Germany, followed by China, with C. on Wilmowsky and X.Y. Ma being the prominent first authors from these countries, respectively. The journal with the most publications was Clinical Oral Implants Research, with an impact factor of 5.021. The most used keywords were “dental implant” and “osseointegration,” which demonstrates the object and the main objective of the studies. In terms of citations, the oldest article contained the highest number, which led to a discussion of factors related to citations such as author collaborations and their influence. Conclusion The bibliometric analysis demonstrated valuable data from implant dentistry studies involving large animals with systemic diseases. Despite the relevance of these articles, the number of published studies on this subject remains small. The focus of the majority of these articles was osseointegration in connection with the development of surface modifications, which involves the area of biomaterials.
Keywords: Animal models; Bibliometrics; Dental implants; Osseointegration; Sheep; Swine